APPROACH CONSTRUCTIVISM ON DESCRIPTION WRITING SKILLS IN INDONESIAN COURSE IN CLASS IV SDN 48 GANTING, PADANG CITY - Destari Martin (LPPM Ekasakti University, 2022)
This study aims to describe the effect of this study. constructivism approach to the descriptive writing skills of fourth-grade students at SDN 48 Ganting, Padang city. The results showed that there was a positive and significant effect of the constructivism approach on the writing skills of the fourth-grade Indonesian students of SD Negeri 48 Ganting, Padang City. This is evidenced by the results of the t-test with a significant level of 5% (0.05) and t count (2.93049) > t table (1.67793). The results of the descriptive writing skill test of Indonesian students obtained by the experimental group were higher than the control group, as indicated by the mean 74.13 and the mean obtained by the control group of 68.00.